2003
DOI: 10.1075/eurosla.3.08nav
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of an earlier start

Abstract: The aim of this paper is to analyse the development of the written production of six groups of learners (N=520) in a formal instruction setting and to investigate the effects of onset and age on the levels of attainment in writing performance. The written production was measured after 200, 416 and 726 hours of instruction. Both intragroup and intergroup analyses were carried out (a) to analyse the long-term effects of an earlier start in second language writing in a school setting, (b) to analyse the patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…For their part, the correlations found between the various measures of written competence used change depending on learners' grade, a finding consistent with results by Navés et al (2003) that showed that the correlations between measures depended on learners' age.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…For their part, the correlations found between the various measures of written competence used change depending on learners' grade, a finding consistent with results by Navés et al (2003) that showed that the correlations between measures depended on learners' age.…”
Section: Resultssupporting
confidence: 86%
“…Those of Knoch et al (2014Knoch et al ( , 2015 found significant writing development but limited to certain measures in students who had spent some period of study abroad. Navés, Torras, and Celaya (2003) and Godfrey, Treacy, and Tarone (2014) also report longitudinal studies, but comparing the performance of different groups. Navés et al (2003) investigated the development of the written production of six groups of primary and secondary education learners using fluency, accuracy, and complexity measures.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in Torras and Celaya (2001) and Celaya et al (2001) indicate an advantage for later learners (i.e., beginning at age 11) with regard to the rate of learning both after 200 hours and after 416 hours, as these students received the highest scores across the four categories. After 726 hours of instruction, the same pattern resurfaced for most of the scales, even though the early learners outperformed the later learners on four of them (Navés et al, 2003). 5 With regard to spoken proficiency, similar results were obtained within the BAF Project.…”
Section: Rate Of Learningmentioning
confidence: 53%
“…2 Several studies were designed with subjects chosen not according to age at the time data were collected (thus in contrast to Boyson et al, 2013;Burstall, 1975;Burstall et al, 1974;Genelot, 1997;Kalberer, 2007;Muñoz, 2011;Oller & Nagato, 1974), but rather according to a similar number of hours of target language instruction; the overall aim was to measure rate of learning rather than L2 attainment. Among these studies are Celaya, Torras, and Pérez-Vidal (2001), Lasagabaster and Doiz (2003), Navés, Torras, and Celaya (2003), and Torras and Celaya (2001) on written proficiency; Mora (2006) and Muñoz (2003) on verbal fluency; and Cenoz (2003) and Miralpeix (2006) on both verbal and written skills.…”
Section: L2 Attainmentmentioning
confidence: 99%